2013
DOI: 10.1039/c3nj00263b
|View full text |Cite
|
Sign up to set email alerts
|

Pendent group effects, PGEs, in P-donor ligands

Abstract: Pendent groups or atoms attached to phosphorus atoms control the latters' behaviour in a variety of ways. Empirical quantitative determination of the extent of back-donation from a variety of metal centres to P-donor ligands is remarkably simple and can be accomplished quickly by comparison with readily available C-O stretching frequencies in Ni(CO) 3 L complexes coupled with pK a data that have been available for many years. However, these estimates are not the whole story and a fourth effect, in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The effects of π backbonding appear in aspects of transition-metal coordination chemistry ranging from evaluation of orbital gaps and the spectrochemical series to the thermodynamic trans influence and the kinetic trans effect. A textbook example involves the trend in M­(CO) 6 q complexes where the extent of backbonding correlates with the carbon–oxygen vibrational stretching frequencies. Experimentally, evaluating relative amounts of π acceptor capacity for different ligand types has proved challenging, mostly because it is difficult to separate σ-bonding and π-bonding effects. Carbonyl carbon–oxygen vibrational stretching frequencies have been used to assess the π backbonding capacities of other ligands bound to the same metal, but care must be taken in selecting ligands, metals, and geometries to obtain trustworthy results. Lichtenberger and coworkers argued that gas-phase photoelectron spectroscopy is the only experimental technique that can quantitatively separate ligand π-bonding effects from σ-bonding and charge potential effects. , Using this technique, they found that CCH – acts as nearly a pure donor toward d 6 CpM­(CO) 2 (M = Fe and Ru) fragments rather than as an acceptor and that SiCl 3 – acts as a modest acceptor in these systems. Recently, Roithová, Rasika Dias, and coworkers used gas-phase bond dissociation to show that alkynes bind coinage metal complexes more strongly than alkenes do, a result they trace to greater backbonding in the former …”
Section: Introductionmentioning
confidence: 99%
“…The effects of π backbonding appear in aspects of transition-metal coordination chemistry ranging from evaluation of orbital gaps and the spectrochemical series to the thermodynamic trans influence and the kinetic trans effect. A textbook example involves the trend in M­(CO) 6 q complexes where the extent of backbonding correlates with the carbon–oxygen vibrational stretching frequencies. Experimentally, evaluating relative amounts of π acceptor capacity for different ligand types has proved challenging, mostly because it is difficult to separate σ-bonding and π-bonding effects. Carbonyl carbon–oxygen vibrational stretching frequencies have been used to assess the π backbonding capacities of other ligands bound to the same metal, but care must be taken in selecting ligands, metals, and geometries to obtain trustworthy results. Lichtenberger and coworkers argued that gas-phase photoelectron spectroscopy is the only experimental technique that can quantitatively separate ligand π-bonding effects from σ-bonding and charge potential effects. , Using this technique, they found that CCH – acts as nearly a pure donor toward d 6 CpM­(CO) 2 (M = Fe and Ru) fragments rather than as an acceptor and that SiCl 3 – acts as a modest acceptor in these systems. Recently, Roithová, Rasika Dias, and coworkers used gas-phase bond dissociation to show that alkynes bind coinage metal complexes more strongly than alkenes do, a result they trace to greater backbonding in the former …”
Section: Introductionmentioning
confidence: 99%